Rumah RANDA: Model Inovasi Desa Ramah Lansia Berbasis Komunitas di Katumbangan - Fredy Akbar K; Syamsidar Syamsidar; Adi Hermawan (Jurnal Pengabdian Masyarakat JUPEMANDO, 2025)
The elderly are a group that is vulnerable to experiencing physical, psychological, social, and spiritual health problems. However, at the village level, integrated services for the elderly are still limited, so it often causes welfare problems. RANDA House Innovation  is present as a strategy to build a community-based Elderly-Friendly Village in Katumbangan Village. This activity aims to design, launch, and implement an integrated service model for the elderly that is integrated with local cultural approaches. The implementation method is carried out through a participatory approach involving the village government, lecturers, students, elderly families, health cadres, and cross-sector stakeholders. The series of activities includes cross-generational education through the Elderly Family School, the implementation of Fine Arts Group Activity Therapy, the empowerment of the elderly economy through product bazaars, and the signing of joint commitments. The results of the activity showed high enthusiasm from the elderly, families, and the village community; increased family knowledge about elderly care; as well as policy support from the village to district levels. RANDA House's innovation can be replicated in other villages as an effort to strengthen the inclusive and dignified quality of life of the elderly.